Pengaruh Sistem Produksi Lean terhadap Pengurangan Biaya Produksi dan Peningkatan Profitabilitas di Industri Pengolahan Limbah Plastik - Radhiana, Radhiana; Mukhdasir, Mukhdasir; Surya, Jen; Syamsuddin, Nurfiani; Maryam, Maryam; Syafitri, Aulia (Jurnal Serambi Engineering, 2025)
The plastics recycling industry plays a vital role in reducing the environmental impact of plastic waste. However, challenges such as high operating costs and low profit margins are hindering its growth. This article explores the application of lean production systems as a potential solution to improve operational efficiency and profitability in this industry. By reducing waste at various stages of production, such as energy consumption, raw materials and production time, lean has been shown to reduce operating costs by up to 10% in large-scale production. In addition, Lean enables companies to increase production capacity without significantly increasing costs. Despite the challenges associated with initial investment and organisational culture change, the long-term benefits of implementing Lean, such as increased profit margins and competitiveness, make it a highly relevant strategy for the plastics recycling industry.